Langkah - Langkah Progresif dalam Intervensi Reduksi Stigma HIV di Komunitas Tenaga Kesehatan: Scoping Review - Triana, Vivi; Effendi, Nursyirwan; Prahastuti, Brian Sri; Ilmiawati, Cimi (Jurnal Kesehatan Komunitas, 2024)
Stigma plays a significant role in creating disparities in health services experienced by PLWHA, thus becoming a barrier for them to access prevention, care, and treatment services. Therefore, the role of health workers is crucial. This study aims to review and critically evaluate the type and scope of interventions that have been conducted to reduce HIV/AIDS-related stigma among health workers. This study is a scoping review using PRISMA guidelines. Journal and article searches were conducted through electronic databases, including ScienceDirect, Cochrane Library, Embase, Garuda Portal, PubMed, Scopus, and Sage Journals. Fourteen articles were discussed in this review. Interventions that successfully reduced stigma were those provided with individual emphasis by disseminating information, interacting, and training. In addition, structural approaches such as developing and disseminating policies in hospitals, providing material to facilitate the practice of universal precautions, and adding curriculum in health schools). The results obtained from the intervention significantly reduced stigma among health workers with a combined approach, which showed higher effectiveness than the single approach. Interventions to reduce stigma need to be sufficiently carried out with an individual-based approach, but interventions with a structural approach must also be considered. Suggest further research by analyzing or exploring potential synergies between these two approaches.